Evaluation of alternative mobility scenarios in the post-COVID-19 period with the use of Multi-Actor Multi-Criteria Analysis (MAMCA). Issue 1 (1st December 2022) - Chrysanidis, Theodoros; Nalmpantis, Dimitrios
Abstract: The emergence, spread, and outbreak of the COVID-19 pandemic, first in the Wuhan city of China but later in the rest of the world, has affected the lives of people all over the world. This inevitable influence has not left the transportation sector unaffected. Therefore, there is a need to examine whether the choices of citizens have been influenced in terms of their mobility. The choice of the optimal solution for each citizen depends on many factors, such as the price of transportation fuel, the safety of going to work, the availability of public transport, the possibility of risk of infection, etc. The mobility choices of the citizens in the pre-COVID-19 era in comparison with the post-COVID-19 era have changed due to the increased vigilance of the citizens. In addition to citizens, other stakeholders are infectious disease experts/epidemiologists, transportation engineers, etc. This is, therefore, a problem that is offered for analysis using Multi-Actor Multi-Criteria Analysis (MAMCA). This research investigates the mobility choices of people in the post-COVID-19 era using the different stakeholder groups and the MAMCA methodology. Useful results arise concerning the influencing factors of the mobility choices of different stakeholder groups in the post-COVID-19 era.